2014
DOI: 10.2196/resprot.2599
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Use and Action Planning in a Web-Based Computer-Tailored Weight Management Program for Overweight Adults: Randomized Controlled Trial

Abstract: BackgroundThere are many online interventions aiming for health behavior change but it is unclear how such interventions and specific planning tools are being used.ObjectiveThe aim of this study is to identify which user characteristics were associated with use of an online, computer-tailored self-regulation intervention aimed at prevention of weight gain; and to examine the quality of the goals and action plans that were generated using the online planning tools.MethodsData were obtained with a randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 59 publications
4
36
0
Order By: Relevance
“…However, overall attrition is a common plague in eHealth interventions, and losses of up to 60–80 per cent of participants have been reported elsewhere (Geraghty, Torres, Leykin, Perez‐Stable, & Munoz, ). Compared to the present study, previous eHealth interventions including planning tools showed a similar number of planning tool users in dietary intake (18–58%) and physical activity (16–64%) (van Genugten, van Empelen, & Oenema, ; Storm et al., ; Van der Mispel et al., ) interventions. In one study, the intervention component with the highest attrition was action planning (compared to other intervention components such as, for example, self‐monitoring) (Van der Mispel et al., ).…”
Section: Discussionsupporting
confidence: 58%
“…However, overall attrition is a common plague in eHealth interventions, and losses of up to 60–80 per cent of participants have been reported elsewhere (Geraghty, Torres, Leykin, Perez‐Stable, & Munoz, ). Compared to the present study, previous eHealth interventions including planning tools showed a similar number of planning tool users in dietary intake (18–58%) and physical activity (16–64%) (van Genugten, van Empelen, & Oenema, ; Storm et al., ; Van der Mispel et al., ) interventions. In one study, the intervention component with the highest attrition was action planning (compared to other intervention components such as, for example, self‐monitoring) (Van der Mispel et al., ).…”
Section: Discussionsupporting
confidence: 58%
“…However, to fit with self-regulation, participants formulated their own goals and plans [ 72 ]. This may have resulted in goals and plans of low quality, as is found in another Web-based computer-tailored intervention [ 73 ]. Goals and plans of low quality may decrease the effects of self-regulation on behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason for finding small ES may be the nonoptimal exposure to the different modules and sessions, which often happens in Internet interventions [ 73 , 74 ]. In addition, participants could choose their own target behavior(s) and were consequently not necessarily exposed to all modules.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the progression and maintenance of the behavior change were targeted in the second and third session of the intervention. However, exposure to these two follow-up sessions was very low, which is often observed in online interventions [ 66 , 67 ]. Consequently, participants may have not sufficiently integrated self-regulation skills in daily life, which may have resulted in not adopting new habits.…”
Section: Discussionmentioning
confidence: 99%